Novel copper-containing ferrite nanoparticles exert lethality to MRSA by disrupting MRSA cell membrane permeability, depleting intracellular iron ions, and upregulating ROS levels - Ye, Jinhua; Hou, Fangpeng; Chen, Guanyu; Zhong, Tianyu; Xue, Junxia; Yu, Fangyou; Lai, Yi; Yang, Yingjie; Liu, Dedong; Tian, Yuantong; Huang, Junyun (Frontiers in Microbiology, 2023)
Objective: The widespread use of antibiotics has inevitably led to the emergence of multidrug-resistant bacterial strains, such as methicillin-resistant Staphylococcus aureus (MRSA), making treatment of this infection a serious challenge. This study aimed to explore new treatment strategies for MRSA infection. Methods: The structure of Fe3O4 NPs with limited antibacterial activity was optimised, and the Fe2+ ↔ Fe3+ electronic coupling was eliminated by replacing 1/2 Fe2+ with Cu2+. A new type of copper-containing ferrite nanoparticles (hereinafter referred to as Cu@Fe NPs) that fully retained oxidation-reduction activity was synthesized. First, the ultrastructure of Cu@Fe NPs was examined. Then, antibacterial activity was determined by testing the minimum inhibitory concentration (MIC) and safety for use as an antibiotic agent. Next, the mechanisms underlying the antibacterial effects of Cu@Fe NPs were investigated. Finally, mice models of systemic and localised MRSA infections was established for in vivo validation. Results: It was found that Cu@Fe NPs exhibited excellent antibacterial activity against MRSA with MIC of 1 µg/mL. It effectively inhibited the development of MRSA resistance and disrupted the bacterial biofilms. More importantly, the cell membranes of MRSA exposed to Cu@Fe NPs underwent significant rupture and leakage of the cell contents. Cu@Fe NPs also significantly reduced the iron ions required for bacterial growth and contributed to excessive intracellular accumulation of exogenous reactive oxygen species (ROS). Therefore, these findings may important for its antibacterial effect. Furthermore, Cu@Fe NPs treatment led to a significant reduction in colony forming units (CFU) within intra-abdominal organs, such as the liver, spleen, kidney and lung, in mice with systemic MRSA infection, but not for damaged skin in those with localised MRSA infection. Conclusion: The synthesised nanoparticles has an excellent drug safety profile, confers high resistant to MRSA, and can effectively inhibit the progression of drug resistance. It also has the potential to exert anti-MRSA infection effects systemically in vivo. In addition, our study revealed a unique multifaceted antibacterial mode of Cu@Fe NPs: (1) an increase in cell membrane permeability, (2) depletion of Fe ions in cells, (3) generation of ROS in cells. Overall, Cu@Fe NPs may be potential therapeutic agents for MRSA infections.